2016
DOI: 10.1002/jbm.a.35954
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer cellular stacks of gelatin‐hydroxyapatite fiber scaffolds for bone tissue engineering

Abstract: Multilayer cellular stacks of crosslinked, electrospun 25 wt % hydroxyapatite (HA)-gelatin and pure gelatin fiber scaffolds, seeded with human fetal osteoblasts (hFOBs), were studied for up to 18 days in static and dynamic cell culture. Two types of stack models were investigated: a four-layer stack with cells seeded at the bottom surface of the first/top layer and the top surface of the fourth/bottom layer, so that the two middle layers were not seeded with cells with the aim to act as continuing conduits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The high degree of fiber alignment in the scaffolds (rather than random fiber orientation of past studies and even better orientation than in our previous study) and the formation of HA‐gelatin nanocomposites (rather than microcomposites of past studies) reinforced the mechanical properties where the 25 wt % HA‐gelatin scaffolds exhibited the highest mechanical performance, a Young's modulus of 0.9 GPa and tensile strength of 10 MPa for scaffolds electrospun at 30 kV, and the best cell proliferation, ECM production and mineralization after 18 days for scaffolds electrospun at 20 kV. As a result of these conclusions, the superior 25 wt % HA‐gelatin scaffolds of this study have been selected to be further investigated in the fabrication of multilayer cellular scaffold stacks for bone tissue engineering …”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…The high degree of fiber alignment in the scaffolds (rather than random fiber orientation of past studies and even better orientation than in our previous study) and the formation of HA‐gelatin nanocomposites (rather than microcomposites of past studies) reinforced the mechanical properties where the 25 wt % HA‐gelatin scaffolds exhibited the highest mechanical performance, a Young's modulus of 0.9 GPa and tensile strength of 10 MPa for scaffolds electrospun at 30 kV, and the best cell proliferation, ECM production and mineralization after 18 days for scaffolds electrospun at 20 kV. As a result of these conclusions, the superior 25 wt % HA‐gelatin scaffolds of this study have been selected to be further investigated in the fabrication of multilayer cellular scaffold stacks for bone tissue engineering …”
Section: Resultssupporting
confidence: 48%
“…As a result of these conclusions, the superior 25 wt % HA-gelatin scaffolds of this study have been selected to be further investigated in the fabrication of multilayer cellular scaffold stacks for bone tissue engineering. 32…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo result in rabbit models confirmed that the scaffolds with patterned membranes manifested favorable biocompatibility and promoted tissue regeneration [201]. Besides trachea, electrospun fibers have been used as scaffolds for a wide range of tissue engineering applications including heart [202][203][204], bone [205][206][207], blood vessels [208][209][210], nerves [211][212][213], cartilage [214][215][216], etc. These fibers are usually combined with growth factors to regenerate lost or damaged tissues.…”
Section: Tissue Engineeringmentioning
confidence: 71%
“…Layer‐by‐layer stacking strategy provides a versatile approach for the fabrication of 3D bone tissue engineering scaffolds by stacking electrospun mats into a thick multi‐layer construct (Salifu, Lekakou, & Labeed, ). By stacking the human adipose‐derived stem cells (ADSCs) seeded PCL/gelatin electrospun mats into a multi‐layer (three layers) 3D construct, the cell distribution in the whole scaffold was homogenous, and in vivo experiment showed that ADSC‐laden paper‐stacking membranes group exhibited the highest osteogenic gene expressions (Wan et al, ).…”
Section: Scaffolds With Encapsulated Cellsmentioning
confidence: 99%